2021
DOI: 10.1037/pag0000428
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging goals to incentivize healthful behaviors across adulthood.

Abstract: Despite abundant evidence for the benefits of physical activity on aging trajectories, older Americans remain largely inactive. The present study was designed to examine age differences in responsiveness to financial incentives to increase walking. Grounded in socioemotional selectivity theory, we examined the effectiveness of financial incentives that varied in prosociality. Three types of incentives were presented to community-residing adults 18 -92 years of age (N ϭ 450). Participants were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
1
17
0
1
Order By: Relevance
“…For instance, our findings could reflect age-related differences in perceived efficacy of distancing and donating during the pandemic or anxiety regarding the economic impact. We believe that our findings transcend the current pandemic and support past empirical and theoretical accounts of increased prosociality among older adults in other contexts [6][7][8][9][10][11][12][13][14][15][16] . Crucially, we demonstrate age-related differences in prosocial behavior in the majority of countries across the globe.…”
Section: Nature Agingsupporting
confidence: 82%
“…For instance, our findings could reflect age-related differences in perceived efficacy of distancing and donating during the pandemic or anxiety regarding the economic impact. We believe that our findings transcend the current pandemic and support past empirical and theoretical accounts of increased prosociality among older adults in other contexts [6][7][8][9][10][11][12][13][14][15][16] . Crucially, we demonstrate age-related differences in prosocial behavior in the majority of countries across the globe.…”
Section: Nature Agingsupporting
confidence: 82%
“…Consistent with this age-related preference for emotional meaning, intriguing neuroimaging evidence indicates that age-related changes in motivation are associated with greater concern for the common good (Mayr & Freund, 2020), suggesting that messages with a focus on social impact may be particularly effective among older segments of the population. A recent study comparing different types of financial incentives aimed at increasing walking found that older people significantly increased their step counts when incentives involved earning money for charities, whereas younger people did not (Raposo et al, 2021).…”
Section: Implications For Effective Communication and Messagingmentioning
confidence: 99%
“…Raposo, S., Hogan, C. L., Barnes, J. T., Chemudupati, T., & Carstensen, L. L. (2021). (See References).…”
Section: Recommended Readingunclassified
“…Findings from two national daily diary studies in the USA suggest that older adults dedicate more time to formal volunteering and unpaid assistance (for example, babysitting or helping with shopping) than younger adults 9 . In a study that examined responsiveness to financial incentives in young, middle-aged and older adults, a, Raposo et al 10 examined age differences in responses to financial incentives to increase walking as measured by accelerometers. In one condition, participants were told that they could earn money for charities by increasing daily step counts.…”
mentioning
confidence: 99%
“…Reproduced by permission from ref. 10 . b, Hubbard et al 12 found a linear association of age with general benevolence as indexed by neural activation.…”
mentioning
confidence: 99%